Chromium (VI) induces toxicity at different photosynthetic levels in pea - Rodriguez, Eleazar (2012)
In order to comprehensively characterize the effects of Cr (VI) on the photosynthetic performance of Pisum sativum, plants irrigated with Cr solutions (ranging from 20 to 2000 mg l(-1)) were evaluated using the following classical endpoints: gas exchange parameters, chlorophyll a (Chl a) fluorescence, leaf pigments, Rubisco activity, soluble sugars and starch content. Flow cytometry (FCM) was applied in an innovative approach to evaluate the morphological and fluorescence emission status of chloroplasts from plants exposed to Cr (VI). The parameters related to gas exchange, net CO(2) assimilation rate (A) and Rubisco activity were severally affected by Cr exposure, in some cases even at the lowest dosage used. While all biomarkers used to measure Chl a fluorescence indicated a decrease in fluorescence at the maximum dosage, pigment contents significantly increased in response to Cr (VI). The morphology of chloroplasts also was altered by Cr (VI) exposure, as a volume decrease was observed. Soluble sugars and starch showed an overall tendency to increase in Cr (VI) exposed plants, but sucrose and glucose decreased highly when exposed to 2000 mg l(-1). In conclusion, our results indicate that Cr (VI) affects photosynthesis at several levels, but the most Cr (VI)-sensitive endpoints were chloroplast morphology and biochemical processes; only at higher dosages the photochemical efficiency is compromised.